ANALISIS KRITIS TEOLOGIS TERHADAP GEREJA TUHAN YANG MAHA KUASA - Selphinus Pariama (STT BIBLIKA JAKARTA, 2026)
The Church of Almighty God has recently become a widely discussed topic. Some groups regard it as a new teaching within Christianity, while others consider it a modern form of heresy. Although its missionary work appears well-organized, some observers believe that its teachings tend not to align with mainstream Christianity. Nevertheless, its activities have spread across many countries, including Indonesia. Therefore, a theological analysis is necessary to gain a proper understanding of the Church of Almighty God’s theological position before drawing personal conclusions for educational purposes. This study employs a biblical approach as the basis for exegesis and interpretation, supported by literature review as a complementary method. The findings indicate that the Church of Almighty God represents a modern form of heresy, with teachings that essentially constitute a selective compilation of various classical doctrines within Christianity, packaged in rhetoric and philosophy